Endobronchial tuberculosis: A case-based approach - Sharma, Rachit; Prasad, Rajendra; Rani, Harshita; Rishabh Kacker; Anshita Chhabra; Singh, Dhruv Raj (Asian Journal of Medical Sciences, 2023)
Endobronchial tuberculosis (TB) or tracheobronchial TB is defined as tuberculous infection of the tracheobronchial tree with microbial and histopathological evidence. Here, in this article, we are reporting four surprising cases of endobronchial TB which came to our institution with clinical symptoms and signs suggestive of TB but chest X-rays were within normal limit and sputum microscopies were repeatedly negative. Bronchoscopy was performed which showed endobronchial lesions. Hence, early diagnosis and treatment were possible for these patients.